If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3x + 4) = 5(5x + -4) Reorder the terms: 7(4 + 3x) = 5(5x + -4) (4 * 7 + 3x * 7) = 5(5x + -4) (28 + 21x) = 5(5x + -4) Reorder the terms: 28 + 21x = 5(-4 + 5x) 28 + 21x = (-4 * 5 + 5x * 5) 28 + 21x = (-20 + 25x) Solving 28 + 21x = -20 + 25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25x' to each side of the equation. 28 + 21x + -25x = -20 + 25x + -25x Combine like terms: 21x + -25x = -4x 28 + -4x = -20 + 25x + -25x Combine like terms: 25x + -25x = 0 28 + -4x = -20 + 0 28 + -4x = -20 Add '-28' to each side of the equation. 28 + -28 + -4x = -20 + -28 Combine like terms: 28 + -28 = 0 0 + -4x = -20 + -28 -4x = -20 + -28 Combine like terms: -20 + -28 = -48 -4x = -48 Divide each side by '-4'. x = 12 Simplifying x = 12
| 12x+4y=20(x) | | 7g+h=-2 | | -6x+5=77 | | 4(3y+6m)+-6y+14m= | | 6+2x=4(x+3) | | 4n+2=-4n+-2 | | 3x^2-28x-20=0 | | 2t+x=19 | | s=t+4 | | 36c^2-84cd+49d^2= | | (2x-10)(x+2)=0 | | 12x+12=72 | | 4x+100=22 | | 7z-2=6x+25 | | 3+x+4+5=10+6x+5-2x | | 7-2x=4x-5 | | 8+4x=20+8x | | 4x^2+24x-448=0 | | [2x-3]=9 | | 3n+3(-n+3)=3 | | -12x+16=-12x+-16 | | 8y=40+3y | | 2(6x-2x)=56 | | 2x^5+4x^4-4x^3-8x^2=0 | | 8x=3(5+x) | | -6x+-3=-6x-2 | | 5z^2+10z=0 | | 6x+20=x+50 | | 12-20=15p+15 | | 9(8y-5)-7(6y+7)=20y | | 3b-3(b-1)=2(3b-1)+6 | | n^2-4n+5=0 |